WATER WISE RICE CULTIVATION ON CALCAREOUS SOIL WITH THE ADDITION OF ESSENTIAL MICRONUTRIENTS - N. Sarwar; H. Ali; A. Ahmad; E. Ullah; S. Ahmad; K. Mubeen; J. E. Hill (Journal of Animal and Plant Sciences, 2013)
Increasing food production and water saving are the major challenges for rice growers at micronutrient deficient soil in Pakistan. Thus the field experiment was conducted focusing on two emerging deficient micronutrients (B and Zn) through soil application in different rice cultures. Application of boron and zinc was done alone and in combination with each other having control treatment in various rice cultures: Aerobic rice, flooded rice and intermittent flooding and drying. Experiment was conducted by using randomized complete block design with split plot arrangements keeping rice cultures in main plot while micronutrients in subplots. Study revealed that the yield attributes (Plant height, productive tillers, panicle length and 1000 kernel weight) of rice crop were significantly hassled when it was subjected to grow in aerobic condition without micronutrients application. However, crop was not affected significantly when it was grown in modified rice culture and performed as good as the normal flooded rice. Rice crop matured in intermittent flooded and drying condition enhanced paddy yield with combined micronutrients application as compared to aerobic culture and resulted in similar performance with flooded rice. Maximum water productivity (0.26, 0.21g/liter) and benefit cost ratio (1.89, 1.72) was recorded in modified rice culture.
Keywords: water productivity; yield attributes; rice; boron and zinc